Intraductal papillary and mucinous pancreatic tumour: a new extracolonic tumour in familial adenomatous polyposis. Issue 3 (1st September 2002) - Maire, F; Hammel, P; Terris, B; Olschwang, S; O'Toole, D; Sauvanet, A; Palazzo, L; Ponsot, P; Laplane, B; Lévy, P; Ruszniewski, P
Abstract : Familial adenomatous polyposis (FAP) is characterised by the development of numerous colorectal adenomatous polyps. Other extracolonic benign or malignant lesions have been reported previously in association with FAP but precancerous lesions in the pancreas have never been described. We report the first case of intraductal papillary and mucinous pancreatic tumour (IPMT) in a patient with FAP. A 48 year old man with a well documented past history of FAP was admitted for epigastric pain, weight loss, and new onset diabetes mellitus. Spiral computed tomography scan revealed a large tumour in the pancreatic head with upstream main pancreatic duct dilatation. Endoscopic ultrasonography confirmed these data. Mucous secretion was seen at duodenoscopy and a lesion in the main pancreatic duct was confirmed by retrograde pancreatography. The patient underwent a pancreaticoduodenectomy for suspected IPMT. Histological examination of the resected specimen confirmed an IPMT with in situ carcinoma. Twelve months after resection, the patient remained free of tumour relapse. Genetic analysis showed loss of the wild allele of the adenomatous polyposis coli gene in IPMT, causing inactivation of both alleles and demonstrating that IPMT was not incidental in this patient. IPMT should be included in the extracolonic localisation of FAP.